Intra-Positional and Inter-Positional Differences in Somatotype Components and Proportions of Particular Somatotype Categories in Youth Volleyball Players - Zoran Grgantov; Johnny Padulo; Mirjana Milić; Luca Paolo Ardigò; Marko Erceg; Drazen Cular (The Society of Aging and Physical Activity (SAPA), 2017)
Objective(s). Main aim of this cross-sectional study was to analyse intra-positional, inter-positional differences in proportions of particular somatotype categories in youth volleyball players. Methods. Heath-Carter method was used to determine somatotype characteristics of 181 young female volleyball players (age 14.05±0.93, height 170.03±7.61 cm, mass 57.80±8.59 kg, body mass index 19.99±2.37 kg/m2, somatotype 4.33-2.79-3.73±1.02-1.02-1.25). Dependent variables were playing position, player efficacy. Only 7 somatotype categories (of possible 13) were obtained. Results. By analysing intra-positional differences, a significantly higher frequency of somatotype categories dominated by the ectomorph component was established in a subsample of more successful players, and a significantly higher frequency of somatotype categories dominated by the endomorph component was found in a subsample of less efficient players. The most frequent somatotype category in all player positions in a sample of more efficient volleyball players is the balanced ectomorph. The smallest number of somatotype categories (only three) was obtained in the subsample of more efficient middle hitters. It indirectly indicates that the most stringent requirements for selection according to the body build are for that position. Similar small inter-positional differences were obtained in both subsamples. Ectomorph somatotype component was most pronounced in young middle-hitters, and endomorph in liberos. Small inter-positional differences in both subsamples are probably consequences of previous selection processes within the clubs. Conclusion. Results obtained in this study provide a clearer insight into inter-positional, intra-positional differences in somatotype categories of young female volleyball players.